Freeze-thaw resistant modified foam concrete and preparation method thereof
By using modified fine-grained steel slag and nanocomposite foam stabilizer in foam concrete, the problem of poor anti-freeze-thaw performance of foam concrete during the freeze-thaw cycle is solved, and its mechanical properties and durability are significantly improved.
Patent Information
- Application Number
- CN202411935553.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Existing foam concrete has poor anti-freeze-thaw performance during the freeze-thaw cycle, which is prone to cracks and reduces durability.
The modified fine steel slag is prepared by adding tetramethylguanidine propyl trimethoxysilane to the wet-grinding raw material of the steel slag, and a nanocomposite foam stabilizer composed of modified nanosilica, hydroxypropyl methylcellulose ether and cationic surfactant is introduced into the foam concrete raw material to coordinate the mechanical properties and durability.
Through the coordinated cooperation of modified fine-ground steel slag and nanocomposite foam stabilizer, the mechanical properties and durability of foam concrete are significantly improved, its anti-freeze and thaw properties are enhanced, and the occurrence of cracks is reduced.
Smart Images

Figure BDA0005211426920000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of foam concrete, and particularly relates to freeze-thaw resistant modified foam concrete and a preparation method thereof. Background Art
[0002] Foamed concrete is a lightweight porous concrete containing a large number of closed pores that is made by introducing air bubbles into the cementitious material slurry through physical or chemical methods and solidifying it. Due to the large number of closed pores inside, foamed concrete has the superior properties of lightness, heat preservation, sound insulation and fire resistance, which can significantly reduce the energy consumption of buildings and has become a research hotspot in the field of civil engineering.
[0003] At present, researchers have conducted extensive research on the raw material components, maintenance system and engineering application of foamed concrete, and have obtained many useful research results. In terms of raw material composition, steel slag, an industrial solid waste discharged from the steelmaking industry, has active ingredients similar to those of silicate cement. Using steel slag as an admixture in foamed concrete can not only absorb steel slag, but also replace part of the cement. At the same time, the micro-expansion characteristics of steel slag can be used to make up for the large shrinkage of foamed concrete, ultimately achieving the goals of energy conservation and emission reduction, turning waste into treasure and protecting the environment.
[0004] For example, patent CN103771797B discloses a foamed concrete block prepared by mixing steel slag with mineral slag and a preparation method thereof. The concrete block is prepared by mixing a slurry with a foaming agent solution, and then forming, demolding and curing. The slurry comprises, by weight, 20-50 parts of steel slag, 20-40 parts of mineral slag, 40-150 parts of cement, 10-70 parts of water, 0-10 parts of an early strength agent, 0-5 parts of a coagulant, 0-2 parts of fiber and 0-6 parts of a water reducer. The foaming agent solution is prepared by mixing and foaming a foaming agent and water in a mass ratio of 1:20-1:60. The volume of foam generated by foaming the foaming agent solution is 30-100 times the volume of the slurry. Patent CN103011723B discloses a large amount of steel slag foamed concrete block and a preparation method thereof. The concrete block is prepared by mixing slurry and foaming agent solution, and then forming, demolding and curing. The slurry comprises, by weight, 50-150 parts of cement, 20-60 parts of steel slag, 10-60 parts of water, 0-8 parts of early strength agent, 0-3 parts of accelerator, 0-1.5 parts of fiber, 0-5 parts of water reducer and 0-5 parts of activator.
[0005] The above is the technology of using ground steel slag as an admixture in foamed concrete, which not only realizes the disposal of solid waste but also achieves the purpose of resource recycling. Because steel slag has low activity, it is often ground to improve its activity. The surface of ground steel slag powder is static. During the preparation of foamed concrete, static steel slag powder is easy to gather and adsorb around the foam, which will affect the mixing uniformity of steel slag powder and cement around the foam, and form stress around the pore wall. Although this stress will not have a great impact on foamed concrete with low mechanical property requirements, during the freeze-thaw cycle, when the water in the pores freezes and expands, the expansion force of the ice and the stress around the pore wall are superimposed on each other, so that the local stress exceeds the tensile strength of the concrete, thereby causing cracks in the concrete. Moreover, once cracks appear, they will expand rapidly in subsequent freeze-thaw cycles, further reducing the freeze-thaw resistance of the concrete.
[0006] Therefore, it is necessary to further improve the foamed concrete with ground steel slag as an admixture to improve the durability of the foamed concrete. Summary of the invention
[0007] In order to solve the problem of poor freeze-thaw resistance of the foamed concrete, the present invention adds tetramethylguanidinopropyltrimethoxysilane to the wet-grinded raw material of steel slag to prepare modified ground steel slag, and introduces a nano-composite foam stabilizer prepared by compounding modified nano silicon dioxide, hydroxypropyl methylcellulose ether and cationic surfactant-triethanolamine monooleate into the foamed concrete raw material. With the synergistic cooperation of the modified ground steel slag and the nano-composite foam stabilizer, foamed concrete with excellent mechanical properties and durability is obtained.
[0008] In order to achieve the above objectives, the following technical solutions are adopted:
[0009] A freeze-thaw resistant modified foam concrete comprises the following raw materials in parts by weight: 30-50 parts of cement, 40-60 parts of modified steel slag, 1-1.5 parts of nano-composite foam stabilizer, 3-5 parts of foaming agent, 25-35 parts of fine aggregate, 3-5 parts of activator, 1-2 parts of early strength agent, 0.3-0.5 parts of water reducer and 80-300 parts of water; the modified steel slag is prepared by adding steel slag, tetramethylguanidinopropyltrimethoxysilane and water in a mass ratio of 100:5-7.5:40-50 to a wet grinder for wet grinding and drying; the nano-composite foam stabilizer is prepared by compounding coupling agent modified nano silicon dioxide, hydroxypropyl methylcellulose ether and alcohol amine ester cationic surfactant in a mass ratio of 3-5:1:3-5.
[0010] The alcoholamine ester cationic surfactant is selected from one or a combination of two or more of triethanolamine monooleate, triisopropanolamine monooleate, and triethanolamine monostearate.
[0011] The coupling agent modified nano silicon dioxide is prepared by a method comprising the following steps: dispersing nano silicon dioxide in a modified liquid to form a mixed liquid, heating the mixed liquid to a reflux state for reaction, and filtering, washing and drying after the reaction to obtain the coupling agent modified nano silicon dioxide.
[0012] The modified liquid is a solution containing 5-10wt% of a silane coupling agent, and the solvent is an organic solvent. The silane coupling agent is selected from one or a combination of aminosilane coupling agents and hydroxysilane coupling agents, preferably an aminosilane coupling agent. The aminosilane coupling agent is selected from one or a combination of two or more of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane. The organic solvent is selected from one or a combination of two or more of benzene and toluene. The silane coupling agent is 5-10wt% of nano-silicon dioxide. The average particle size of the nano-silicon dioxide is 20-50nm. The mass fraction of nano-silicon dioxide in the mixed solution is 40-60wt%. The washing is 1-3 times of washing with ethanol. The drying is drying at 80-100°C to constant weight.
[0013] The viscosity of the hydroxypropyl methylcellulose ether is 80,000-100,000 Pa·s.
[0014] The grinding body used in the wet grinding is a ceramic ball with a mass ratio of 1.1-1.2mm:0.7-0.8mm:0.5-0.6mm=1-3:2-4:1-3; the wet grinding time is 0.5-1h, and the rotation speed is 200-500r / min. The drying is dried at 60-100°C to constant weight.
[0015] The median particle size of the modified steel slag is 1-5 μm.
[0016] The basicity of the steel slag is 1.4-2.4, and the steel slag is selected from one or a combination of two or more of converter steel slag, open-hearth steel slag, and electric furnace steel slag.
[0017] During the wet grinding process, adding an appropriate amount of tetramethylguanidinopropyltrimethoxysilane can form a conductive channel on the surface of the modified ground steel slag, eliminate static electricity, prevent excessive steel slag powder from gathering and adsorbing around the foam, reduce stress concentration, and play a positive role in improving durability.
[0018] However, the inventors found that modifying the ground steel slag with tetramethylguanidinopropyltrimethoxysilane not only did not improve the durability, but also reduced the mechanical properties of the foamed concrete. Only after adding an appropriate amount of a nano-composite foam stabilizer composed of modified nano-silica, hydroxypropyl methylcellulose ether, and cationic surfactant in a mass ratio of 3-5:1:3-5, was a foamed concrete with excellent mechanical properties and durability obtained. It is speculated that the use of tetramethylguanidinopropyltrimethoxysilane is equivalent to grafting a long-chain structure containing guanidine groups on the surface of steel slag. Compared with the case where it is not used, the phenomenon of aggregation and adsorption around the foam and the degree of stress concentration have been improved to a certain extent, and there will be no problem of excessive aggregation and adsorption; but it does not rule out the possibility that the modified ground steel slag is adsorbed with the foam. Once it is adsorbed with the foam, it will be integrated into the foam liquid film and become a part of the liquid film; because the particle size of the modified ground steel slag is still relatively large, it has rigidity and low surface energy. This characteristic has a negative impact on the elastic strength of the foam liquid film, so that when the liquid film is subjected to external force, the buffering and deformation capacity are weakened, the stability of the foam is reduced, resulting in an increase in the connected pores of the foam concrete, a decrease in the mechanical properties, and a poor durability improvement effect.
[0019] The nano-composite foam stabilizer, which is made of modified nano-silica, hydroxypropyl methylcellulose ether and cationic surfactant in a specific ratio, can effectively protect the foam from three dimensions: steric hindrance, physical barrier and charge barrier. Among them, hydroxypropyl methylcellulose ether can form a tough and high-strength film layer around the foam to build steric hindrance; modified nano-silica forms a physical barrier with its tiny particle characteristics; and cationic surfactants rely on their own charges to generate a charge barrier. The three work together to ensure the stability of the foam.
[0020] The cement is silicate cement with a strength grade of 42.5-52.5.
[0021] The activator is selected from one or a combination of two or more of calcium hydroxide, sodium hydroxide and sodium carbonate.
[0022] The early strength agent is selected from one or a combination of two or more of sodium formate, sodium acetate and triethanolamine.
[0023] The water reducing agent has a water reducing rate of 18-25%, and is selected from one or a combination of two or more of polycarboxylic acid water reducing agents and naphthalene water reducing agents.
[0024] The foaming agent is a physical foaming agent, which is selected from one or a combination of two or more of rosin resins, synthetic surfactants, and proteins.
[0025] Furthermore, the foaming agent is a synthetic surfactant.
[0026] Furthermore, the foaming agent is sodium dodecylbenzene sulfonate.
[0027] The fine aggregate is quartz sand with a fineness modulus of 2.2-2.4.
[0028] The present invention also provides a method for preparing modified foamed concrete, comprising the following steps:
[0029] 1) adding a foaming agent and a nano-composite foam stabilizer into water for dilution, and then adding the dilution into the foaming agent for foaming to obtain foam;
[0030] 2) Mix cement, modified ground steel slag, fine aggregate, activator, early strength agent, water reducing agent and water to obtain a mixture;
[0031] 3) Add foam to the mixture and stir to obtain modified foam concrete.
[0032] Step 1) The mass ratio of the foaming agent to water is 1:30-50.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The invention prepares modified ground steel slag by adding tetramethylguanidinopropyltrimethoxysilane into wet-grinded raw materials of steel slag, and introduces a nano-composite foam stabilizer prepared by compounding modified nano silicon dioxide, hydroxypropyl methylcellulose ether and cationic surfactant-triethanolamine monooleate into foamed concrete raw materials. With the synergistic cooperation of the modified ground steel slag and the nano-composite foam stabilizer, foamed concrete with excellent mechanical properties and durability is obtained. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0036] Electric furnace slag was purchased from Hebei Wenfeng Industrial Group Co., Ltd. with a basicity of 2.0.
[0037] Nano-silicon dioxide with an average particle size of 20 nm was purchased from Beijing Solebow Technology Co., Ltd., item number NM000840.
[0038] SSF-1000 series naphthalene-based high-efficiency water-reducing agent has a water-reducing rate of 21.8% and was purchased from Hubei Shanshufeng Building Materials Technology Co., Ltd.
[0039] Hydroxypropyl methylcellulose ether has a viscosity of 100,000 Pa·s and was purchased from Shanghai Kelaman Reagent Co., Ltd.
[0040] Example 1
[0041] S1) preparing modified ground steel slag: adding steel slag, tetramethylguanidinopropyltrimethoxysilane and water in a mass ratio of 100:7.5:50 to a wet grinder, wet grinding at a speed of 500 r / min for 1 h using ceramic balls with a mass ratio of 1.2 mm:0.8 mm:0.6 mm=2:3:1, and drying at 60° C. to constant weight to obtain modified ground steel slag with a median particle size of 3.6 μm;
[0042] S2) Preparation of modified nano-silica: 500 g of nano-silica NM000840 was dispersed in 1000 g of a modified liquid prepared by mixing 3-aminopropyltrimethoxysilane and benzene in a mass ratio of 5:95, stirred to form a stable suspension, heated to reflux state and reacted for 24 h. After the reaction was completed, filtered, washed with ethanol 3 times, and dried at 100° C. to constant weight to obtain modified nano-silica.
[0043] S3) preparing modified foamed concrete:
[0044] S31) 500g of sodium dodecylbenzene sulfonate and 150g of a nano-composite foam stabilizer prepared by mixing modified nano-silicon dioxide, hydroxypropyl methylcellulose ether and triethanolamine monooleate in a mass ratio of 5:1:3 are added to 15kg of water for dilution, and then the dilution is added to a foaming agent for foaming to obtain foam;
[0045] S32) 3000g cement, 6000g modified ground steel slag, 2500g quartz sand with a fineness modulus of 2.2, 500g sodium hydroxide, 200g sodium formate, 50g SSF-1000 series naphthalene-based high-efficiency water reducing agent, and 4500g water are mixed to obtain a mixture;
[0046] S33) adding the foam from step S31) to the mixture from step S32) and stirring to obtain modified foamed concrete.
[0047] Example 2
[0048] The rest is the same as Example 1, except that in step S31), the amount of the nano-composite foam stabilizer is 100 g.
[0049] Example 3
[0050] The rest is the same as Example 1, except that in step S31), the mass ratio of modified nano-silica, hydroxypropyl methylcellulose ether, and triethanolamine monooleate is 5:1:5.
[0051] Example 4
[0052] The rest is the same as Example 1, except that in step S31), the mass ratio of modified nano-silica, hydroxypropyl methylcellulose ether, and triethanolamine monooleate is 3:1:3.
[0053] Example 5
[0054] The rest is the same as Example 1, except that in step S31), the mass ratio of modified nano-silica, hydroxypropyl methylcellulose ether, and triethanolamine monooleate is 3:1:5.
[0055] Example 6
[0056] The rest is the same as Example 1, except that in step S2), 3-aminopropyltrimethoxysilane is replaced by an equal mass of hydroxymethyltriethoxysilane.
[0057] Example 7
[0058] S1) preparing modified ground steel slag: adding steel slag, tetramethylguanidinopropyltrimethoxysilane and water in a mass ratio of 100:7.5:50 to a wet grinder, wet grinding at a speed of 500 r / min for 1 h using ceramic balls with a mass ratio of 1.2 mm:0.8 mm:0.6 mm=2:3:1, and drying at 60° C. to constant weight to obtain modified ground steel slag with a median particle size of 3.6 μm;
[0059] S2) Preparation of modified nano-silica: 500 g of nano-silica NM000840 was dispersed in 1000 g of a modified liquid prepared by mixing 3-aminopropyltriethoxysilane and benzene in a mass ratio of 5:95, stirred to form a stable suspension, heated to reflux state and reacted for 24 h. After the reaction was completed, filtered, washed with ethanol 3 times, and dried at 100° C. to constant weight to obtain modified nano-silica.
[0060] S3) preparing modified foamed concrete:
[0061] S31) 500g of sodium dodecylbenzene sulfonate and 100g of a nano-composite foam stabilizer prepared by mixing modified nano-silicon dioxide, hydroxypropyl methylcellulose ether and triethanolamine monooleate in a mass ratio of 5:1:5 are added to 15kg of water for dilution, and then the dilution is added to a foaming agent for foaming to obtain foam;
[0062] S32) 5000g cement, 4000g modified ground steel slag, 2500g quartz sand with a fineness modulus of 2.4, 300g sodium hydroxide, 200g sodium formate, 50g SSF-1000 series naphthalene-based high-efficiency water reducing agent, and 4500g water are mixed to obtain a mixture;
[0063] S33) adding the foam from step S31) to the mixture from step S32) and stirring to obtain modified foamed concrete.
[0064] Example 8
[0065] The rest is the same as Example 1, except that, in step S1), steel slag, tetramethylguanidinopropyltrimethoxysilane and water are added to the wet grinder in a mass ratio of 100:5:50.
[0066] Comparative Example 1
[0067] The rest is the same as Example 1, except that in step S31), the nanocomposite foam stabilizer is replaced by an equal mass of conventional foam stabilizer hydroxypropyl methylcellulose ether.
[0068] Comparative Example 2
[0069] The rest is the same as Example 1, except that in step S1), the wet grinding medium is all water and does not contain a quaternary ammonium silane coupling agent.
[0070] Comparative Example 3
[0071] The rest is the same as Example 1, except that in step S1), the wet grinding medium is all water and does not contain a quaternary ammonium silane coupling agent; in step S31), no nano-composite foam stabilizer is added.
[0072] Comparative Example 4
[0073] The rest is the same as Example 1, except that in step S31), the cationic surfactant-octadecylamine acetate is used instead of the cationic surfactant-triethanolamine monooleate with an equal mass.
[0074] The foamed concrete prepared in the above examples and comparative examples was cured under standard conditions and then subjected to the following performance tests:
[0075] Compressive strength: The test was conducted in accordance with the standard JG / T 266-2011 foam concrete. The test equipment was NYL-2000 pressure testing machine to conduct 28d compressive strength test.
[0076] Freeze-thaw cycle: refer to the slow freezing method in the standard GB / T 50082-2009 Test method for long-term performance and durability of ordinary concrete, and cycle 50 times. One cycle includes: dropping from 25℃ to -25℃ for 4h, keeping constant at -25℃ for 4h, rising from -25℃ to 25℃ for 2h, keeping constant at 25℃ for 2h, then re-measure the compressive strength and calculate the 28d compressive strength loss rate.
[0077] Pore structure analysis: Prepare a 100mm×100mm×100mm specimen, cut it in half, take photos of the interface size of 11mm×9mm using a DJCK-2 crack width gauge from Precision Instruments, mark the holes using image processing software Image ProPlus, perform pore structure analysis using image processing software Namo Measurer, and record the average roundness value.
[0078] Uniformity: Prepare a cylindrical specimen with a diameter of 5 cm and a height of 1 m, take out a small cylinder with a height of 3 cm from the bottom and top of the specimen, and calculate its density. According to the following formula, the larger the value of the top density / bottom density of the sample, the worse the uniformity.
[0079] R=ρ 底 / ρ 顶
[0080] Table 1 Performance test results
[0081]
[0082] It can be seen from Example 1 and Comparative Examples 1-3 in Table 1 that the nanocomposite foam stabilizer has the effect of reducing the pore size and significantly synergistically modifying the ground steel slag to improve the uniformity and roundness of the pores, and further, improves the strength of the foamed concrete and improves the durability.
[0083] It can be seen from Example 1 and Examples 3-5 that changing the mass ratio of modified nano-silica, hydroxypropyl methylcellulose ether, and triethanolamine monooleate will produce a significant change in the average roundness value. Only when the mass ratio of the three is 5:1:3, the average roundness value is closest to 1, indicating that the nano-composite foam stabilizer has a significant synergistic isolation effect. When the modified ground steel slag is close to the foam, the nano-composite foam stabilizer can prevent the modified ground steel slag from directly contacting the foam to the greatest extent, thereby improving the stability of the foam.
[0084] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A freeze-thaw resistant modified foam concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 30-50 parts of cement, 40-60 parts of modified steel slag, 1-1.5 parts of nano-composite foam stabilizer, 3-5 parts of foaming agent, 25-35 parts of fine aggregate, 3-5 parts of activator, 1-2 parts of early strength agent, 0.3-0.5 parts of water reducer and 80-300 parts of water; the modified steel slag is prepared by adding steel slag, tetramethylguanidinopropyltrimethoxysilane and water in a mass ratio of 100:5-7.5:40-50 to a wet grinder for wet grinding and drying; the nano-composite foam stabilizer is prepared by compounding coupling agent modified nano silicon dioxide, hydroxypropyl methylcellulose ether and alcohol amine ester cationic surfactant in a mass ratio of 3-5:1:3-5.
2. The freeze-thaw resistant modified foam concrete according to claim 1, characterized in that: The alcoholamine ester cationic surfactant is selected from one or a combination of two or more of triethanolamine monooleate, triisopropanolamine monooleate, and triethanolamine monostearate.
3. The freeze-thaw resistant modified foam concrete according to claim 1, characterized in that: The coupling agent modified nano silicon dioxide is prepared by a method comprising the following steps: dispersing nano silicon dioxide in a modified liquid to form a mixed liquid, heating the mixed liquid to a reflux state for reaction, and filtering, washing and drying after the reaction to obtain the coupling agent modified nano silicon dioxide.
4. The freeze-thaw resistant modified foamed concrete according to claim 3, characterized in that: The average particle size of the nano silicon dioxide is 20-50 nm.
5. The freeze-thaw resistant modified foamed concrete according to claim 3, characterized in that: The silane coupling agent is selected from one or a combination of aminosilane coupling agents and hydroxysilane coupling agents, preferably an aminosilane coupling agent; the aminosilane coupling agent is selected from one or a combination of two or more of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane.
6. The freeze-thaw resistant modified foamed concrete according to claim 1, characterized in that: The viscosity of the hydroxypropyl methylcellulose ether is 80,000-100,000 Pa·s; the basicity of the steel slag is 1.4-2.4, and the slag is selected from one or a combination of two or more of converter slag, open-hearth slag, and electric furnace slag.
7. The freeze-thaw resistant modified foamed concrete according to claim 1, characterized in that: The grinding body used in the wet grinding is a ceramic ball with a mass ratio of 1.1-1.2mm:0.7-0.8mm:0.5-0.6mm=1-3:2-4:1-3; the wet grinding time is 0.5-1h, and the rotation speed is 200-500r / min; the median particle size of the modified steel slag is 1-5μm.
8. The freeze-thaw resistant modified foamed concrete according to claim 1, characterized in that: The foaming agent is a physical foaming agent, which is selected from one or a combination of two or more of rosin resins, synthetic surfactants, and proteins.
9. The method for preparing the modified foamed concrete according to any one of claims 1 to 8, characterized in that: The steps include: 1) adding a foaming agent and a nano-composite foam stabilizer into water for dilution, and then adding the dilution into the foaming agent for foaming to obtain foam; 2) Mix cement, modified ground steel slag, fine aggregate, activator, early strength agent, water reducing agent and water to obtain a mixture; 3) Add foam to the mixture and stir to obtain modified foam concrete.
10. The method for preparing modified foamed concrete according to claim 9, characterized in that: Step 1) The mass ratio of the foaming agent to water is 1:30-50.
Citation Information
Patent Citations
Heavily-doped steel slag foam concrete building block and preparation method thereof
CN103011723B
Preparation Method of Foamed Concrete Blocks with Steel Slag and Mineral Slag
CN103771797B
Heavily-doped steel slag foam concrete building block and preparation method thereof
CN103011723A
Foam concrete masonry block prepared by double doping of steel slag and mineral waste residues and preparation method thereof
CN103771797A
Pervious concrete additive and pervious concrete
CN107686274A